Falske nyheter, alternative fakta og sleipe knep - Nils Ivar Agøy (Heimen)
Abstract From ca. 1870 to ca. 1900 mass meetings constituted a primary political arena in Norway, a place where political careers could be made and destroyed. National politics was exceedingly polarized during this period. In the years up to 1884, a heterogeneous opposition challenged the sitting government, demanding that parliament should be given much more influence on both cabinet composition and day-to-day policy. The struggle was finally won by the opposition in 1884, and resulted in the formation of a Liberal party (the former opposition) and a Conservative party. The next twenty years saw new bitter fights concerning mainly Norway's position in its union with Sweden and the principle of parliamentarianism. The mass meetings served to mobilize ordinary voters in an age without a truly national press, but were characterized by heckling, insults, manipulation and the use of outright lies to such a degree that they can hardly have served as tools to help undecided people form an opinion. It is argued that their main function was very different, to prod participants into joining one of the two blocs by largely emotional appeals, where “truth” and reasoned argument mattered far less than the sense of belonging.